Physiological Response on Broiler Chicken’s Liver Supplemented Amino Acid Metionine-Cystine in Feed Contaminated with Aflatoxin B1 - Listya Purnamasari; Ali Agus; Cuk Tri Noviandi (Journal of Livestock Science and Production, 2019)
The content of AFB1 in feed with low levels and spend a long time, will cause primary damage or primary liver carcinoma. This study aims to reduce the toxicity of AFB1 with amino acid methionine-cystine supplementation in broiler chicken feed. This study used a 3 × 3 factorial design with methionine-cystine amino acid levels (M + C: 75, 100 and 125%) and AFB1 levels (0, 200, and 400 ppb). The variables collected were liver physiology, liver histopathology, SGPT levels, and SGOT levels. Observations of liver physiology showed that feed containing aflatoxin without methionine-cystine amino acid had a paler yellowish color (T4, T7 and T8). Pathological examination resulted that aflatoxicosis will attack the liver. Transition amino acid cystines in chicken feed contaminated with AFB1 did not occur in blood SGPT levels. Blood SGOT levels were highest at 21 days of age, namely T2 (M + C 100%) and T3 (M + C 125%) at AFB1 0 ppb which showed excess liver damage. The administration of methionine-cystine amino acids of 75, 100 and 125% in chicken feed contaminated with AFB1 0, 200 and 400 ppb consumed by broilers carries a risk of physiological and pathological damage to chicken liver.